EPID-10. EVOLVING SURVIVAL TRENDS IN INFANTS WITH BRAIN TUMORS: A LONGITUDINAL POPULATION BASED STUDY. Issue 2 (22nd June 2018) - Faltermeier, Claire; Chai, Timothy; Elkaim, Lior; Ibrahim, George; Wang, Anthony; Weil, Alexander; Bendel, Anne; Fallah, Aria; Tu, Albert
Abstract: Management of brain tumors in infants has evolved over time, however, historical prognostication does not reflect current treatment and survival trends. This study used a population-based approach to differentiate contemporary from historical survival curves to provide up-to-date prognostication. METHODS: Observational cohort analysis was performed using the Surveillance, Epidemiology and End Results (SEER) database. Infants with brain tumors from 1973-2013 were divided by tumor subtype (diffuse astrocytic/oligodendroglioma, choroid plexus, embryonal, ependymal, medulloblastoma and pilocytic astrocytoma). The 1, 5 and 10 year survival was stratified by decade. Trends in management and outcomes were analyzed. RESULTS: Between 1973 and 2013, 2996 patients <24 months were identified. All tumor types except embryonal and choroid plexus demonstrated improved survival with time. Infants with embryonal tumors showed a decline in survival between the 1970s and 1990s (p= 0.008). Infants with choroid plexus tumors had no change in survival over time. The greatest improvement in survival was seen for infants with ependymal tumors, with 5-year survival improving from 28% (95% CI 15-42%) in the 1980s to 77% (95% CI 69-83%) the 2000s. Radiation therapy declined from 1970 to 2000 for all tumors, however, radiation treatment for embryonal and ependymal subtypes has increased since 2000. CONCLUSIONS: Despite improved overall survival from the 1970s onwards, certain subtypes of infant brain tumors have not matched this trend. The use of radiation has declined, although in specific tumor types, its use has been associated with better survival. Prognostication in infants with brain tumors should be updated to reflect current treatment trends.